Strategi Komunikasi Wanita dalam Film Barbie - Sitinjak, Vivi Novalia; S. Meliala, Grace Cya Aprilia; Sihombing, Riska Wati; Simamora, Maria Yosepine (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study, conducted in a sociolinguistic setting, looks into the communication strategies utilized by female characters in the animated film "Barbie and the Magic of Pegasus." It looks at how these characters' verbal choices reflect and maybe perpetuate gendered norms and expectations, building on Coates' theory of conversational strategies. The study uses a qualitative analysis minimal responses, tag questions, questions, hedges, commands and directives, swearing and taboo language, as well as compliments used by the female characters in the film. This improves comprehension of the complicated connections between children's stories, language, gender, and social interaction. The goal is to provide a deeper understanding of the communicative preferences exhibited by these characters. Looking at women's words can reveal a lot about how gender identities are constructed and transmitted in animated storytelling. This study not only enriches the sociolinguistic academic discourse but also prompts a profound reflection on the role of language in shaping social norms. By providing a nuanced perspective on the communicative strategies of female characters, this research invites critical engagement with the dynamics of language, gender, and social interactions within the realm of animated narratives. This allows us to think more deeply about societal communication in movies. The results of this study indicate that women show characteristics of a gentler communication style with the use of limited gentle responses, subtle tag questions, and limited application of compliments. This preference prioritizes inclusion and brevity of communication over other techniques such as instructions, hedging, and taboo language. Keywords: Coates Theory, Communication Strategies, Female Characters